Water strider algorithm: A new metaheuristic and applications. (June 2020) - Kaveh, A.; Dadras Eslamlou, A.
Abstract: The present paper proposes a novel nature-inspired optimization paradigm, which is called the Water Strider Algorithm (WSA). The WSA is a population-based optimizer inspired by the life cycle of water strider bugs. The WSA mimics territorial behavior, intelligent ripple communication, mating style, feeding mechanisms and succession of water striders. The algorithm is mathematically formulated and benchmarked on forty-four numerical problems, four classic examples, two large scale structural size optimization and one structural damage identifying applications. In two phases, the algorithm is investigated to prove its promising performance against possible biases. Different parametric and nonparametric tests, as well as comparison with well-established and state of the art algorithms, indicate the efficient performance of the proposed WSA. The algorithm is applied to classical constrained, unconstrained, continuous and discrete structural design problems confirming its capability of tackling various challenging problems. The paper also presents a real application of the proposed method in structural health monitoring, in which the WSA effectively identified the damage scenarios.